Satisfaction of adult and pediatric neurologists and neurosurgeons using telehealth during the COVID-19 pandemic in Saudi Arabia: a cross-sectional study - Algarni, Saleh Ayed; Alrashid, Maha Hamoud; Aldayel, Mohammed Sultan; Allowaihiq, Lujain Habeeb; Almuqbil, Abdulaziz Ali; Albarrak, Anas Mohammad; Almobarak, Sulaiman (Frontiers in Digital Health, 2024)
Telehealth has become increasingly important in achieving universal health coverage. It offers doctors and their patients' convenience, including providing quality care at reduced costs. During the COVID-19 pandemic, telehealth has been a vital tool for remote healthcare services. This study aimed to assess the satisfaction of adult and pediatric neurologists and neurosurgeons using telehealth, during the COVID-19 pandemic in Saudi Arabia.This study had 348 participants. It was conducted among adult and pediatric neurologists and neurosurgeons using telehealth technology at their clinics between February and June 2021. A self-administered questionnaire included sociodemographic data, behavior in using telehealth, and an assessment of satisfaction with telehealth; the SPSS Windows software version 26 was used to analyze the data.The most common age group was 25-34 years (42.8%), with men dominating (68.4%). The mean satisfaction score was 25.9 (SD 3.91) out of 33 points, with 90.2% of respondents satisfied with telehealth and 9.8% dissatisfied. Working in an academic center or private hospital, being a first-time telehealth user, using messages as a telehealth method, and using telehealth daily were associated with increased satisfaction with telehealth use.Adult and pediatric neurologists' and neurosurgeons' satisfaction with telehealth was high.Physicians still preferred face-to-face interviews but recognized the benefits of telehealth in strengthening the patient-provider relationship, improving productivity, and integrating into daily workflows. Satisfaction levels align with past studies, but physical examination needs should be considered. Telehealth is suitable for follow-up visits and varies across subspecialties.